Religiosity and attitude influence on muslims' intention to visit homestays in Sabah, Malaysia / Azrin Jalasi and Sylvia Nabila Azwa Ambad - Jalasi, Azrin; Sylvia Nabila, Azwa Ambad (Universiti Teknologi MARA, Kedah, 2022)
Homestay is another vital tourism product that the government of Malaysia has emphasized. However, homestays without specific Shari'ah regulation have caused conflicts and inconveniences for Muslim guests. Therefore, this study examines religiosity and attitude on the Muslims' intention to visit homestays in Sabah, Malaysia. A quantitative cross-sectional approach was applied to gather data from a sample of 251 Malaysian Muslims, and a convenience sampling method is employed to collect data for the study. Data collected were analyzed using SmartPLS 3.3.2.9 software. The study's findings indicate that religiosity and attitude significantly influence the Malaysian Muslims' intention to visit homestays in Sabah, Malaysia. The study also provides empirical evidence for the individual factor that religiosity and attitude are influencing the Muslims' intention to visit homestays in Sabah, Malaysia. Nonetheless, the scope of the study is limited to Malaysian Muslims' intention to visit homestays in Sabah only.